John Locke and the uncivilized society individualism and resistance in America today - Robinson, Scott 1981- (Lexington Books, 2021)
"This book analyzes the effect of John Locke's political thought on American political culture today. By analyzing nearly the entirety of Locke's political and philosophical writings, this book shows that Locke's thought has helped to cultivate the incivility seen in recent years in American politics"--
Keywords: Locke, John -- 1632-1704; Geschichte 2021; Politisches Denken; Politische Kultur; Einfluss; USA; Locke, John / 1632-1704 / Influence; Political culture / United States; Interpersonal conflict / United States; United States / Politics and government / Philosophy; Locke, John / 1632-1704; Influence (Literary, artistic, etc.); Interpersonal conflict; Political culture; Politics and government; United States